EFISIENSI PAKAN DAN PERTAMBAHAN BOBOT BADAN AYAM KUB YANG DIBERI FITOBIOTIK DENGAN BERBAGAI KONSENTRASI - Sami, Amrullah; Fitriani, F (Journal Galung Tropika, 2019)
Today's consumer tastes tend to choose products that are safe and healthy. However, farmers continue to make efforts to more efficiently utilize feed and have good health. This study aims to determine the effect of phytobiotic administration on drinking water on the efficient use of feed and body weight gain of Kampung Unggul Balitnak (KUB) chickens with different concentrations. Phytobiotics used are a combination of extraction of medicinal plants, namely moringa leaves, aloe vera leaves, betel leaves, papaya leaves, and lemongrass leaves. Phytobiotic is given to drinking water. This study used a Completely Randomized Design (CRD) which was repeated three times with three levels of treatment (0 cc/l, 15 cc/l, 15 cc/l, and 20 cc/l drinking water). Analysis of variance shows that different concentrations have a very significant effect on the efficiency of feed use and have a significant effect on body weight gain of superior Balitnak chickens (KUB). Giving phytobiotics in drinking water with a concentration of 20 cc / l of drinking water can increase the efficiency of feed use (4.98 kg/head/week) and body weight gain of KUB chickens (0.84 kg/head/week).